Implementation Of Criminal Decisions Against Children In Fighting The Law At Takengon District Court - Alianur, Mudfar; Nurlaila, Nurlaila; Sanola, Maria; Rahmawati, Desi (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2025)
The punishment for a child is a special sentence imposed by a judge, apart from imprisonment, in the verdict that the sentence does not need to be carried out due to certain conditions. In the judge's ruling on juvenile punishment, it is stated in Law No. 11 of 2012. This research examines how judges consider sentencing children in conflict with the law at the Takengon District Court in cases with the same circumstances but different verdicts. In this research writing, the researcher uses the normative legal research method, which is an approach based on primary legal materials by examining theories, concepts, legal principles, and regulations related to this research. This approach is also known as the library approach, where the researcher studies the judge's considerations in criminal decisions against children in the same case. The result of this research is that the legal basis for conditional sentences and imprisonment for children has been regulated in the Child Criminal Justice System Law No. 11 of 2012, which states all procedures for handling juvenile criminal cases from the investigation stage, guidance, until the completion of the sentence. As for the legal reasons behind the judge's decision, conditional sentences and prison sentences must be reviewed from several aspects, such as social and economic factors that can influence the judge's considerations, including supporting facilities.